2016
DOI: 10.4209/aaqr.2015.12.0683
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Parametric Study of Frequency and Sound Pressure Level on the Acoustic Coagulation and Precipitation of PM2.5 Aerosols

Abstract: The efficiency of particle removal for PM 2.5 aerosols using conventional separation systems is generally low. In this paper, acoustic precipitation and coagulation of aerosols as a preconditioning system is investigated experimentally. The results of experimental study concerning the effect of frequency and sound pressure level (SPL) on the acoustic coagulation and precipitation of PM 2.5 aerosols are presented. An acoustic particle conditioning setup was used to perform experiments at the resonance frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Fundamentally, PM 2.5 emissions from stationary sources are classified as "filterable" and "condensable'' particulate matter. 10 Filterable fine particulate matter (FPM) is directly emitted from a source as a solid or liquid at stack, and captured on filter media. Condensable particulate matter (CPM) is known as a vapor phase material at stack conditions, but the material can condense and/or react upon cooling in the air to form a solid or liquid PM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamentally, PM 2.5 emissions from stationary sources are classified as "filterable" and "condensable'' particulate matter. 10 Filterable fine particulate matter (FPM) is directly emitted from a source as a solid or liquid at stack, and captured on filter media. Condensable particulate matter (CPM) is known as a vapor phase material at stack conditions, but the material can condense and/or react upon cooling in the air to form a solid or liquid PM.…”
Section: Introductionmentioning
confidence: 99%
“…12−14 Numerous studies have confirmed that CPM contributes significantly to total PM 2.5 emissions from stationary sources. [10][11][12]15 Some studies have evaluated PM 2.5 emissions from industrial coal-fired boilers. 16,17 These studies illustrate characteristics of the emissions from coal-fired boilers, but very few have been carried out to examine emission of oil-fired boilers, 18,19 and to compare the dissimilarities of PM 2.5 emissions and the emission characteristics from coal-and oil-fired boilers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the agglomeration efficiency and collision efficiency of particles increases with an increase of SPL, 27,48,49 because the velocity of the gas medium correspondingly increases rapidly, which leads to an increase in the relative motion speed between the particles. However, when particles collide and form aggregates under the action of a high-intensity sound wave eld, the aggregates are easily separated if the SPL is too high.…”
Section: Calculation Of Separation Of Agglomeratesmentioning
confidence: 99%
“…11 illustrates an experiment in which the pressure drop of charged particles in a reversed electric field was 10% lower than that of filtration-uncharged particles and 5% higher than that of filtration-charged particles. The pressure drop declined when electrostatic materials were added to fibrous filters because charged particles tend to form a notably porous dust cake on the surface of the filter bag (Amiri et al, 2016). The negative polarity electric field of the collection stage rejected the negatively charged particles; thus, the pressure drop of charged particles in that reversed electric field was higher than that of filtration-charged particles.…”
Section: Pressure Dropmentioning
confidence: 99%